3(x*x+2x)=9

Simple and best practice solution for 3(x*x+2x)=9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x*x+2x)=9 equation:


Simplifying
3(x * x + 2x) = 9

Multiply x * x
3(x2 + 2x) = 9

Reorder the terms:
3(2x + x2) = 9
(2x * 3 + x2 * 3) = 9
(6x + 3x2) = 9

Solving
6x + 3x2 = 9

Solving for variable 'x'.

Reorder the terms:
-9 + 6x + 3x2 = 9 + -9

Combine like terms: 9 + -9 = 0
-9 + 6x + 3x2 = 0

Factor out the Greatest Common Factor (GCF), '3'.
3(-3 + 2x + x2) = 0

Factor a trinomial.
3((-3 + -1x)(1 + -1x)) = 0

Ignore the factor 3.

Subproblem 1

Set the factor '(-3 + -1x)' equal to zero and attempt to solve: Simplifying -3 + -1x = 0 Solving -3 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + -1x = 0 + 3 Combine like terms: -3 + 3 = 0 0 + -1x = 0 + 3 -1x = 0 + 3 Combine like terms: 0 + 3 = 3 -1x = 3 Divide each side by '-1'. x = -3 Simplifying x = -3

Subproblem 2

Set the factor '(1 + -1x)' equal to zero and attempt to solve: Simplifying 1 + -1x = 0 Solving 1 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -1x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -1x = 0 + -1 -1x = 0 + -1 Combine like terms: 0 + -1 = -1 -1x = -1 Divide each side by '-1'. x = 1 Simplifying x = 1

Solution

x = {-3, 1}

See similar equations:

| (x+4+2i)(x-4-2i)=0 | | (9p)-(4p)=30 | | 42t^3-14t+51t-17=0 | | 3z=z+12 | | -20+11y=10y | | -4x+5(-4)=19 | | 3x-15+123=180 | | 7x-14/3=14 | | 2 = b3– 2 | | (2x2)12/3 | | (2x2)12/4 | | 7c-42=y | | 42=4w+14 | | 15/100=x/40 | | 9/3*3 | | 6c-8=30 | | 3=9-2h | | x(1.5x)=147 | | 45=10x+5 | | Cos(x/1.25) | | 15x-(3x-3)= | | -7x-2(-5)=-18 | | 12x+9y=150 | | (16/25)-3/2 | | 32-10x=14+8x | | A^2=8a+7 | | 2(6t+1)-11=t-(t+8) | | 2x1/-3 | | (x-4)+7=63 | | 7u^2+28u^3-10u^4-40u^5=0 | | 2.666666667x-2=.6666666667x-12 | | -(x-6)-2x=10 |

Equations solver categories